Process Optimization and Flavor Components Analysis of Rice Crust with Yellow Tea - Mengfei LI; Tao YANG; Jiejie WANG; Yang GAO; Yue SUN; Xueling LI; Zhengquan LIU; Jin LIANG (Shipin gongye ke-ji, 2022)
In order to increase the flavor of rice crust and improve the nutritional value of products, rice and yellow tea were used as raw materials to develop rice crust with yellow tea. The process formula was optimized by response surface methodology, and the quality characteristics of rice crust with yellow tea were analyzed. The results showed that the optimum technological formula of rice crust with yellow tea was as follows: Rice as the base weight, yellow tea powder of 2.5%, potato starch of 20%, baking temperature 195 ℃, baking time 14 min. Under the optimized conditions, the comprehensive score of rice crust with yellow tea was 70.07±0.17, close to the theoretical predicted value. Based on electronic nose and gas chromatography ion mobility spectrometry (GC-IMS), 51 volatile flavor compounds including aldehydes, alcohols, ketones, esters, heterooxygenates and sulfur compounds were detected. In addition, the addition of yellow tea would reduce the in vitro digestibility of rice crust and increase the content of resistant starch. The results of this study provide a theoretical reference for the development of rice crust products rich in yellow tea and the analysis of flavor components.